Design, Synthesis, and Evaluation of Heat Shock Protein 90 Inhibitors in Human Breast Cancer and Its Metastasis - Gümus, Mehmet; Ozgur, Aykut; Tutar, Lutfi; Disli, Ali; Koca, Irfan; Tutar, Yusuf (Current Pharmaceutical Biotechnology, 2016)
Background: Despite development of novel cancer drugs, invasive ductal breast carcinoma and its metastasis are still highly morbid. Therefore, new therapeutic approaches are being developed and Hsp90 is an important target for drug design. For this purpose, a series of benzodiazepine derivatives were designed and synthesized as novel Hsp90 inhibitor. Methods: Benzodiazepine derivatives anticancer activities were determined by XTT cell proliferation assay against human breast cancer cell line (MCF-7). Effects of the compounds on endothelial function were monitored on human vascular endothelium (HUVEC) cell line as well. In order to determine the anti-proliferative mechanism of the compounds, in silico molecular docking studies were performed between Hsp90 ATPase domain and the benzodiazepine derivatives. Further, these compounds perturbation on Hsp90 ATPase function were tested. Fluorescence binding experiments showed that the derivatives bind Hsp90 effectively. Expression analysis of known cancer drug target genes by PCR array experiments suggest that the benzodiazepine derivatives have remarkable anticancer activity. Results: A representative Benzodiazepine derivative D5 binds Hsp90 with Kd value of 3,93 μM and with estimated free energy of binding -7.99 (kcal/mol). The compound decreases Hsp90 ATPase function and inhibit Hsp90 client protein folding activity. The compound inhibits expression of both Hsp90 isoforms and key proteins (cell cycle receptors; PLK2 and TERT, kinases; PI3KC3 and PRKCE, and growth factors; IGF1, IGF2, KDR, and PDGFRA) on oncogenic pathways. Conclusion: Benzodiazepine derivatives presented here display anticancer activity. The compounds effect on both breast cancer and endothelial cell lines show their potential as drug templates to inhibit breast cancer and its metastasis.
Keywords: bone cancer